#TITLE_ALTERNATIVE# - HANIF DIORIZKY (NIM : 10512054), MUHAMMAD
Superoxide Dismutase is a metalloenzyme that converts superoxide radicals to less dangerous species such as hydrogen peroxide (H2O2) dan oxygen (O2). Superoxide radicals can cause various degenerative diseases. This in turns, prompt researchers in medical or natural sciences fields to study SOD mimetics from transition metals complexes. In this research, the potential of Mn(III)salphen complexes as SOD mimetics was studied. A Schiff base salphen (a salen derivative ligand) has been synthesized from 1,2-diaminobenzene and salycilaldehyde to give 85.35% yields. The 1H NMR spectra of the salphen compound showed singlet signals at the chemical shifts of 8 and 13 ppm which was originated from H atom of Ã‚Â–OH and HC=N groups. Two Mn(III)-salphen complexes have been synthesized from its Mn(II) salts and salphen ligand in stoichiometric ratio of 1:1 to form Mn(III)-salphen chloride (1) (77.04% yields) and Mn(III)-salphen acetate (2) (64.48% yields). UV/Vis spectra and magnetic moments of both complexes showed that the Mn(II) ion was oxidized to Mn(III) in the complexes. The SOD bioactivity assay using non-enzymatic riboflavine/NBT method showed that the IC50 value for each complex are 10.60 μM (1) and 10.09 μM (2). The voltammograms resulted from cyclic voltammetry measurements showed that each complex have E1/2 value of 0.027 V (1) and 0.075 V (2) which was within the SOD working range. These results showed that both Mn(III)-salphen complexes have the potential as SOD mimetics.